Light controlled biomaterials for regulating cell migration and differentiation - Changhao Tian; Junsheng Zhang; Jie Gu; Wenfei Li; Yi Cao (Smart Materials in Medicine, 2022)
Cell microenvironments in human body are always complex, dynamic, and asymmetric. Light-controlled materials can mimic different physical and chemical environments non-invasively, in site, and dynamically, as a result, is attracting increasing attention in tissue engineering, cancer biology, and regenerating medicine. In this review, we discuss different light-controlled materials regulating cell behaviors. By controlling mechanical or cell adhesion properties, these materials synthesized by functional proteins or light-sensitive chemical groups can mimic microenvironments and regulate cell behaviors like migration and differentiation.